Cetak rompak produk optik di Malaysia: Antara tuntutan sivil dan sabitan jenayah - Abd Aziz, Ahmad Shamsul (Universiti Utara Malaysia, 2006)
Piracy in film, music and computer software in Malaysia is not a new phenomenon but it has deterionated recently. Advanced technology has made piracy activities possible especially if it is recorded in digital optical disc. Law regarding this matter has been reviewed to curb the piracy activities. Provisions in Copyright Act 1987 and Optical Disc Act 2000 which relates to the problem will be discussed especially regarding the civil action manner and also the criminal conviction.